Formation damage during drilling and completion practices - a review - Md. Yassin, Abu Azam (Faculty of Chemical & Natural Resources Engineering, 1988)
A review of formation damage during drilling indicates that the mechanism of fluid filtration occur in 3 stages i.e. invasion by spurt loss: initial external and internal bridging and filter cake build up. The constituent of the filter cake build up. The constituent of the filter cake and its deposition mechanism crucially controls the extend of formation damage, but during drilling process continues erosion of the surface of the cake occur resulting in dynamic filtration.